PEMAHAMAN TERHADAP HADIS DENGAN PENDEKATAN LINGUISTIK - Wulandari, Susi; Muhid, (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2022)
The purpose of this research is as a scientific contribution in the approach to the science of hadith in to make it easier to understand the hadith mainly in terms of language, because language is a very important, component in knowing various things, for this reason in this study specifically the understanding of hadith with a linguistic approach is discussed. The method used in this paper is to use a linguistic approach, which is a type of qualitative research with literature review. The data was collected from various scientific works, namely the book and the journal, with other. Data collected with documentation and analysis techniques using a hadith science approach that focuses on a linguistic approach. The results and conclusions in this study are that the linguistic approach in understanding hadith is the method used to understand hadith by conducting language analysis as a process of interpreting opinions or some opinions about the intent or meaning contained in it, while understanding hadith using a linguistic approach can be done in the first way, understand difficult words that are suspected to be bi al-makna narration, the second use Gharib al-Hadith Science, the third distinguish the essential hadith and majazi, the fourth trace the asbabul wurud hadith Tujuan dari penelitian ini sebagai kontribusi keilmuan dalam pendekatan ilmu hadis agar dapat memudahkan memahami hadis utamanya dari segi bahasa, sebab bahasa merupakan komponen yang sangat urgen dalam mengetahui berbagai hal, untuk itu dalam penelitian ini secara spesifik dibahas pemahaman terhadap hadis dengan pendekatan linguistik. Metode yang digunakan dalam tulisan ini ialah menggunakan pendekatan linguistic, yang termasuk jenis penelitian kualitatif dengan kajian kepustakaan. Pengambilan data tersebut dari berbagai karya ilmiah yakni kitab, buku dan jurnal beserta data lainnya yang dilakukan pengumpulan menggunakan teknik dokumentasi serta analisis menggunakan pendekatan ilmu hadis yang terfokus pada pendekatan linguistic. Hasil serta kesimpulan dalam penelitian ini ialah pendekatan linguistic dalam memahami hadis merupakan cara yang digunakan untuk memahami hadis dengan melakukan analisis bahasa sebagai proses interpretasi pendapat maupun beberapa pendapat tantang maksud ataupun makna yang terdapat didalamnya, Sedangkan dalam memahami hadis menggunakan pendekatan linguistik dapat dilakukan dengan cara pertama, memahami kata-kata sukar yang ditengarai sebagai riwayat bi al-makna kedua, menggunakan Ilmu Gharib al-Hadis ketiga, membedakan hadis hakiki dan majazi keempat, menelusuri asbabul wurud hadis.